PELATIHAN TARI DASAR BETAWI UNTUK MAHASISWA HEBEI INTERNATIONAL STUDIES UNIVERSITY - Selly Oktarini; B Kristiono Soewardjo; Eko Hadi Prayitno; Vanya Zelia (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract Hebei International Studies University, is one of UNJ's partners which is located in China, precisely on Hongqi road no. 1218, Yuanshi County, Shijiazhuang city, Hebei Province. Hebei International Studies University has several faculties in it, one of which is International Finance. Various study programs at the faculty require students to take Indonesian language courses. This course is held continuously from semester 1 to semester 7. Studying Indonesian makes them interested in the arts and culture of Indonesia, especially since there are several arts in Indonesia that have cultural acculturation with China, such as Betawi Basic Dance. Basic Betawi Dance training will be held at the International Finance Faculty located in Shijiazhuang city, Hebei Province. The object is 79 International Finance Department students. The method used in conducting this dance training is Demonstration and example, namely a training method carried out by direct demonstration and explanation of Basic Betawi Dance. Students will do work through demonstrated examples or experiments, where this method will be very effective because the participants see firsthand the dance techniques used by the instructor. Keywords: Dance Training, Betawi Dance, Basic Betawi Dance Abstrak Hebei International Studies University, merupakan salah satu mitra UNJ yang terletak di negera China, tepatnya di Hongqi road no. 1218, Yuanshi County, Shijiazhuang city, Hebei Province. Hebei International Studies University memiliki beberapa fakultas di dalamnya, salah satunya adalah International Finance. berbagai program studi yang ada di fakultas tersebut mewajibkan mahasiswa untuk mengambil mata kuliah Bahasa Indonesia. Mata kuliah tersebut diselenggarakan secara berkelanjutan dari semester 1 hingga semester 7. Mempelajari Bahasa Indonesia membuat mereka tertarik dengan Seni dan Budaya yang dimiliki Indonesia, terlebih ada beberapa kesenian di Indonesia yang memiliki akulturasi budaya dengan China seperti Tari Dasar Betawi. Pelatihan Tari Dasar Betawi akan dilaksanakan di Fakultas International Finance yang terletak di Shijiazhuang city, Hebei Province. Objeknya adalah Mahasiswa International Finance Department sebanyak 79 orang. Metode yang digunakan dalam melakukan pelatihan tari ini adalah Demonstration and exampel yaitu metode latihan yang dilakukan dengan cara peragaan dan penjelasan secara langsung tentang Tari Dasar Betawi. Mahasiswa akan mengerjakan sesuatu pekerjaan melalui contoh atau percobaan yang didemonstrasikan, dimana metode ini akan sangat efektif karena para peserta melihat langsung Teknik dalam menari yang dilakukan instruktur. Kata kunci: Pelatihan Tari, Tari Betawi, Tari Dasar Betawi